Pengaruh Profitabilitas, Struktur Aktiva, Dan Pertumbuhan Penjualan Terhadap Harga Saham Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun - Wiji Astuti; Risal Rinofah; Pristin Primasari (Jurnal Sosial Ekonomi Bisnis, 2022)
This study aims to determine the effect of profitability, asset structure, and sales growth on stock prices with capital structure as an intervening variable in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesian stock exchange in 2015-2021. The population in this study were 85 manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX). The sampling method used is purposive sampling method, in order to obtain 58 sample companies with 7 years of observation so that the total sample is 406 data for 7 years. The research data were obtained from sample companies which were downloaded from the Indonesia Stock Exchange website. The data analysis method used in this research is descriptive analysis, classical assumption test, multiple linear regression test, hypothesis testing, determinant coefficient test, and path analysis test (path analysis). Based on the results of data processing through the IBM SPSS Statistic Software that has been analyzed, the results of this study are that profitability has an effect on stock prices. Asset structure has no effect on stock prices. Sales growth has no effect on stock prices. And the results of data processing obtained from path analysis (path analysis), concluded that the capital structure has no effect on profitability, asset structure, and sales growth through the stock price.